Steric and Stereoelectronic Effects in Organic Chemistry - Yadav, Veejendra K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The steric and stereoelectronic effects control the rate and stereochemical outcome of reactions. Hence, a decent understanding of the related concepts is essential for successful synthetic planning. The book attempts to address several important issues related to these concepts in a simplified manner, and is intended for graduate students. It lays stress on the important aspects of steric and stereoelectronic effects and their control on the conformational profile and reactivity features. The book covers the geometrical requirements for reactions at saturated and unsaturated carbons in both cyclic and acyclic systems, and the resultant stereochemical features. The aspect of geometrical flexibility is also covered with a few examples involving intramolecular reactions. It deals with the facial selectivity of nucleophilic additions to acyclic and cyclic carbonyl compounds, and explains how the steric and stereoelectronic effects control the same. The work comments on allylic strains and their stereochemical control on different reactions with the related conformational control. It is a must read to understand the control elements, the prominent among these elements are spiro-conjugation, periselectivity, torquoselectivity, a-effect, Hammett's substituent constants, Hammond postulate, and Curtin-Hammett principle.
Steric and Stereoelectronic Control of Organic Molecular Structures and Organic Reactions -- Reactions at Saturated and Unsaturated Carbons -- Diastereoselectivity in Organic Reactions -- A(1,2) and A(1,3) Strains -- The Conservation of Orbital Symmetry (Woodward-Hoffmann Rules) -- The Overlap Component of the Stereoelectronic Factor vis-à-vis the Conservation of Orbital Symmetry Rules -- Miscellaneous.
Keywords: Chemistry, Organic; Physical chemistry; Organic Chemistry; Physical Chemistry